TRANSLATION THEORY AS A BASIC OF TRANSLATION LEARNING: A QUALITATIVE-ETHNOGRAPHIC STUDY - Ninip Hanifah (LPMPP Universitas Negeri Yogyakarta, 2016)
Tujuan penelitian adalah untuk memahami pentingnya penguasaan teori penerjemahan dalam pembelajaran penerjemahan. Penelitian menggunakan metode etnografi dengan pendekatan kualitatif. Data diperoleh melalui observasi, wawancara, dan dokumentasi, sedang analisis data dilakukan secara kualitatif lewat 12 langkah. Hasil penelitian menunjukkan bahwa: (1) teori terjemahan harus dikuasai mahasiswa agar tujuan pembelajaran tercapai dan harus disesuaikan dengan konteks budaya bahasa sumber; (2) berbagai strategiperludigunakan; (3) materi dalam silabus disusun dari tataran yang mudah ke tataran yang sulit; (4) materi pembelajaran dikembangkan dengan media pembelajaran yang dapat memotivasi mahasiswa; (5) dosen dan mahasiswa bekerja sama menciptakan situasi belajar yang kondusif; (6) penggunaan sarana prasarana dan media pembelajaran cukup memadai; (7) evaluasi hasil didasarkan pada keakuratan, kewajaran, dan kejelasan teks. Kata Kunci: teori terjemahan, pembelajaran penerjemahan, etnografiTRANSLATION THEORY AS THE FOUNDATION OF TRANSLATION LEARNING: A QUALITATIVE-ETHNOGRAPHIC STUDYAbstract: The objective of this study is to comprehensively understand the importance of translation theory for learning translation. The study uses qualitative ethnographic method. The data were collected through observation, interview, and documentation, while the analysis was carried out qualitatively through 12 steps. The study demonstrates that: (1) translation theory should be mastered by students to achieve the learning goals and should be adapted to theculturalcontext of the source language, (2) various strategies need to be implemented; (3) materials in the syllabus need to be deliveredfrom the easy levelto thedifficult one, (4) teaching materialsneed to be developedusing appropriatelearning media which can motivate students, (5) conducive environment needs to be created collaboratively by lecturer and students, (6) infrastructure and learning media need to be usedadequately, (7) evaluation needs to be based on accuracy, naturalness, and clarity of the texts.Keywords: translation theory, ethnography